PENGUATAN KOMPETENSI GURU DALAM PENYUSUNAN MEDIA VISUAL DIGITAL DI DESA TOYOMARTO KECAMATAN SINGOSARI KABUPATEN MALANG - Hardinata, Vanda (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2022)
Toyomarto Village has educational facilities ranging from elementary school to high school, including 5 elementary school/MI buildings (SDN Toyomarto I, SDN Toyomarto II, SDN Toyomarto III, SDN Toyomarto IV, and MI Al-Ma'arif 06), 1 junior high school building (SMP Islam Al-Ma’arif 02), and 1 vocational high school building (SMK Insan Mandiri). Efforts to improve the quality of education and enhance teachers’ competencies to achieve greater intelligence and competitiveness involve focusing on enhancing the quality of the learning process through digital integration in the 4.0 era, specifically by developing digital visual teaching materials for the learning process. The strengthening of teachers' competencies in developing digital visual media, particularly in Toyomarto Village, aims to improve the quality of education, especially the quality of learning, by enhancing teachers' competencies in preparing teaching materials for the learning process. Therefore, the community service team conducted community service activities in the form of workshops/training with educational institutions at all levels of education related to “Strengthening teachers' competencies in developing digital visual teaching media in Toyomarto Village, Singosari District, Malang Regency.” Furthermore, this synergistic planning for educational quality development will have a positive impact on improving strategies, planning, media, and evaluation of learning in the Indonesian Language and Literature Education Study Program. The outcome of this activity is training in the creation of digital-based teaching media that teachers can apply in the learning process. Keywords: teacher competence; digital visual media; Toyomarto Village